The Effects of Ripening Stage and Mode of Culture of Chemlali, Arbequina and Koroneiki on the Capacities of Oils to Scavenge ABTS Free Radicals - Jellali, Mourad; Dhouha Naija, Saidana; Samia Gueddes, Ben Mansour; Braham, Mohamed (European Scientific Journal, ESJ, 2022)
The aim of this study is to evaluate the antioxidant power of the olive oil against the cation radical ABTS•+, according to cultivars: Chemlali, Arbequina and Koroneiki; culture modes: extensive and intensive; ripening stages: November and December corresponding stages and study year: 2017 and 2018. Radical percentage inhibition (PI), Trolox equivalent antioxidant capacity (TEAC), inhibitory concentration required to scavenge 50% of radicals (IC50) and principal component analysis (ACP) were determined. The oil of the Tunisian main cultivar Chemlali, cultivated in extensive mode, has the best scavenging power with the lowest IC50 values of 9.3, 10.8, 9.65 and 10.4 µg/ml respectively in all the ripening stages. Also, at the lowest tested concentration of 20 µg/ml, this oil has the highest TEAC values, respectively 2.28 and 2.20 in November of 2017 and 2018. For the introduced cultivars, Koroneiki presents better performance than Arbequina, in intensive mode, with IC50 ranged from 9.6 to 13.8 against 12.40 to 22.35 for Arbequina. Furthermore, the principal component analysis proves that the oils of Chemlali in extensive mode and Koroneiki in intensive have the best scavenging capacity of ABTS•+. This study proves that the extensive mode is the best culture mode and the ripening stage of November is the best stage in order to get oils with a height antioxidant capacity.